PENGARUH PENGETAHUAN WAJIB PAJAK, KESADARAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR RODA DUA DI KECAMATAN SAMBAS - Kartika Sari; U. Sulia Sukmawati; Abdurachman (CV. Adiba Aisha Amira, 2025)
One source of government revenue is revenue from the tax sector. Motor Vehicle Tax (PKB) is one of the regional taxes that contributes significantly to financing provincial development. This study aims to determine the effect of taxpayer knowledge, taxpayer awareness and tax sanctions on taxpayer compliance in paying motor vehicle tax at the Sambas Regency SAMSAT office. The number of samples in this study was 40 samples. The sample determination was carried out using the accidental sampling method, which is a technique for determining samples by chance. Data collection was carried out using the questionnaire method.The data analysis technique used was multiple linear regression analysis. The results of this study indicate that the variable of taxpayer awareness has a significant effect on taxpayer compliance, while the variables of taxpayer knowledge and tax sanctions do not have a significant effect on taxpayer compliance. The results of multiple regression show Y = 13,446 + 0.463. The magnitude of the influence of taxpayer knowledge, taxpayer awareness and tax sanctions on taxpayer compliance of two-wheeled motor vehicles is seen from the R-square of 0.194, meaning that variables X1, X2 and X3 influence Y by 19.4% and the remaining 80.6% is influenced by other variables not examined in this study. While for the simultaneous test based on the results in the ANOVA table shows that the significant value is 0.049 so that <0.05. So based on the hypothesis that H4 is accepted. Thus, variables X1, X2 and X3 influence variable Y so that the result is taxpayer knowledge, taxpayer awareness and tax sanctions influence taxpayer compliance of two-wheeled motor vehicles in Sambas Regency.